Dielectric properties measurement and pH analysis for drinking water - Seok, Y.B.; Hoon, W.F.; Jack, S.P.; Seng, L.Y.; Keng, L.O. (2021)
Every material has its own dielectric properties and it is also the same for water. In this research, dielectric properties measurement on water will be done to examine the water quality of drinking water whether it is safe to drink or not. Water quality in Malaysia, as well as access to water in general, is a major problem. The primary pollutants present in the water are oils, rubbish, suspended solids, sewage and toxic substances. These are consequences of untreated or only partially treated sewage caused by human activities. Thus, water quality in Malaysia is currently of some concern. The normal drinking water pH range mentioned in World Health Organization (WHO) and National Drinking Water Quality Standards (NDWQS) guidelines is between 6.5 and 8.5. The water may contain some residue even though the pH is in the range of 6 to 7.5 so it does not prove that the water is safe enough for drinking purpose. Thereby, the analysis about the water quality using the specific measuring instruments need to carry out to prove that the water in neutral pH may not be safe to drink as the pH does not prove the content of the water as clearly as dielectric properties. High Temperature Coaxial Probe as the dielectric properties measurement sensor will be used to provide better information compare to pH. The measurement parameters that had been used to determine the water quality is the dielectric constant. The results obtained from both pH and dielectric properties measurement values are been analyzed and compared and it shows that pH value for clean and contaminated water is at almost similar values while dielectric properties results show different for both clean and contaminated water.